(untitled) (New York, NY., 2002)
Fifteen philosophers, social scientists, and academic lawyers assess various aspects of bioethics. Some detail its development and challenge the field's basic assumptions. Others consider bioethics's role in contemporary society and examine it in policy administration as well as in its interaction with other branches of philosophical inquiry. Chapters also focus on specific issues, including the responsibilities of researchers to subjects in clinical trials; the proper criteria for determining when a living organism has died; the allocation of scarce, life-saving medical resources; and the subsidization of pharmaceutical products for those who may be deprived of the benefits of modern medicine.
Keywords: Medical ethics,Bioethics,Đạo đức ngành Y,Đạo đức sinh học